Alih Fungsi Lahan Pertanian Menjadi Kawasan Pemukiman Di Kecamatan Polewali Kabupaten Polewali Mandar - Rustan Ir; Muhammad Syaeba (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
Transfer of Agricultural Land Function into Settlement Area in Polewali Mandar District Polewali District. Increasing the number of residents indirectly affects the amount of housing demand. The construction of housing areas in Polewali Subdistrict, Polewali Mandar Regency has increased along with population growth. For these activities, developers often utilize and convert agricultural land. In this case the Regional Government through the RTRW Regulation No.2 of 2013 concerning the 2012-2032 Polewali Mandar District Spatial Plan has a role in regulating and controlling the use of agricultural land. This study uses a qualitative method with a descriptive approach. In this study the results showed that the conversion of agricultural land to the construction of residential areas was regulated in the establishment of spatial patterns for residential areas, while the percentage of agricultural land diverted to housing was 2,091 ha with uneven distribution in all Polewali Mandar Districts.